Three Training Programs in Sex Counseling - McConnell, Lawrence G. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper outlines three training programs in sex counseling. Each program involves five weekly two-hour sessions. They are similar in content but different in method. The three models are labeled didactic, experiential and conjoint. The didactic method involves a series of lectures.The experiential model provides the participants with the opportunity to encounter a variety of sex counseling situations. The conjoint approach incorporates both the didactic and the experiential components. The paper also provides preliminary evidence concerning the relative effectiveness of the three models. It is suggested that the programs be implemented on a trial basis as modules of regular practicum courses in counselor education.